Co-researching co-creation of the curriculum: Reflections on arts-based methods in education and connections to healthcare co-production - Lubicz-Nawrocka, Tanya Michelle; Simoni, Hermina (International Journal for Students as Partners, 2018)
Learning through experience is an important, creative, and fulfilling way to apply theory to practice. In this essay, we explore our experiences of co-researching how students and staff conceptualise co-creation of the curriculum. We each have multi-faceted roles in higher education as we study, work, and contribute to formal student representation processes. At the time of this project, I (Tanya) was working at the Edinburgh University Students’ Association, supporting student representation, and I (Hermina) was a first-year student representative from the School of Health in Social Science. It was through a University of Edinburgh Innovative Initiative Grant project related to Tanya’s PhD research (focusing on co-creation of the curriculum) that we began to work together closely. We are both passionate about becoming involved in collaborative initiatives that improve the student experience and the wider university community. We were interested in exploring how our individual experiences as co-researchers could bridge boundaries between the traditional roles of postgraduate and undergraduate students, staff and students, and researchers and participants. Our aim was to blur the lines between these roles by working collaboratively with students-as-partners, facilitating open dialogue about best practices in learning and teaching, and redistributing power to create new synergies. Below, we focus on these topics and the little-explored connections between our academic disciplines in which co-creation of higher education curricula and co-production of health care are each beginning to play important roles. We reflect on our experiences of engaging in collaborative research using deliberative-democratic and arts-based methods, and we aim to provide an informative account of our experiences while drawing new connections.